2021
DOI: 10.1111/ppc.12964
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nurses' perceptions of conscience and perceptions of individualized nursing care: A cross‐sectional study

Abstract: To identify the relationship between the perception of conscience and individualized nursing care. Design and Methods:A cross-sectional study. The sample of the study consisted of 326 nurses working in internal medicine and surgical clinics. The data were collected using the Nurses' Perceptions of Conscience Questionnaire and Individualized Care Scale-Nurse (ICSA) Version.Findings: Their mean score for the ICSA-Nurse was 3.96 ± 0.72. There was a statistically significant positive correlation between their scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…When nurses follow their conscience to provide quality care, they have a positive view of it, but the conflict caused by conscience can lead to confusion and is associated with guilt ( 28 ). A study conducted by Yildirim et al concluded that the understanding of conscience and the impact of conscience on the nurse-patient relationship can make nurses more sensitive to patient care and at the same time improve the quality of nursing care ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…When nurses follow their conscience to provide quality care, they have a positive view of it, but the conflict caused by conscience can lead to confusion and is associated with guilt ( 28 ). A study conducted by Yildirim et al concluded that the understanding of conscience and the impact of conscience on the nurse-patient relationship can make nurses more sensitive to patient care and at the same time improve the quality of nursing care ( 29 ).…”
Section: Discussionmentioning
confidence: 99%